PENINGKATAN PATIENT SAFETY DENGAN KOMUNIKASI SBAR - Sukesih -; Yuni Permatasari Istanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Hospital patient safety is a system where hospitals make patient care safer. The system includes: risk assessment, identification and treatment related to patient risk. One of the six programs targeting patient safety is effective communication. Effective communication is the key for nurses to achieve patient safety based on the standards of patient safety in hospitals. One method of effective communication is communication SBAR. SBAR communication (Introduction, Situation, Background, Assessment, Recommendation) is communication using a logical tool to organize information so it can be transferred to others accurately and efficiently. The purpose of this study was to determine the effectiveness of the SBAR communication on patient safety. Used literature search using keywords comunication SBAR, pastient safety, is the independent variable and the dependent variable comunication SBAR is patient safety. Searches performed on the website Proquest, PMC, PubMed, or other websites which use the Google Scholar. From the search results in getting as much as ten journals related to the theme. From the tenth to the journal is a journal of clinical research. Results of the literature review found that of the ten journals mention SBAR communication can improve patient safety.Keywords: Comunication SBAR, Patient safety.